Power training: specificity of the exercise mode in performance transfer, external load control and use of the stretch-shortening cycle - Gheller, Rodrigo Ghedini (2023)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2023.